Proposal of a Model of Disaster Medical Education for Practical Risk Management and Disaster Nursing: The SINCHI Education Model - Shinchi, Koichi; Matsunaga, Hitomi; Fukuyama, Yumi (Prehospital and disaster medicine, 2019)
Education in disaster nursing and risk management is important, and developing the human resources of medical staff who participate in disaster response is also necessary. However, a practical educational model for risk management and disaster nursing has not yet been established in Japan. In the present study, a model of disaster medical education for practical risk management and disaster nursing was proposed. Seventeen expert nurses with experience in practical international disaster response (IDR) participated in this study. They were recruited from among past members of Japan disaster response medical teams. They were asked an open-ended question through a questionnaire survey: “What kind of nursing education is necessary for risk management and practical activities in disaster response?” The responses were analyzed qualitatively and an educational model was developed. Sixty-five codes were obtained from the answers to the open-ended question, and they were categorized into 19 sub-categories and three categories. Subsequently, the “SINCHI education model” was proposed for practical disaster nursing education; it comprises six elements: (1) Simulation exercise and small-group work; (2) International nursing knowledge; (3) Nursing skills and knowledge, including disaster nursing; (4) Communication ability promotion; (5) Humanity, responsibility, and flexibility; and (6) Infection prevention and control. A sample of this education exercise model is the following: (1) preparing the list of medical staff members (2) information-gathering simulation (3) preparing the list of medical instruments, and (4) developing the plan for risk management and operation, including infection prevention and control. Disaster nursing education could be made more instructive and practical by including simulation exercises.